Stock Market Structure and Volatility - Stoll, Hans R.; Whaley, Robert E. (Review of Financial Studies, 1990)
The procedure for opening stocks on the NYSE appears to affect price volatility. An analytical framework for assessing the magnitude of the structurally induced volatility is presented. The ratio of variance of open-to-open returns to close-to-close returns is shown to be consistently greater than one for NYSE common stocks during the period 1982 through 1986. The greater volatility at the open is not attributable to the way in which public information is released since both the open-to-open return and the close-to-close return span the same period of time. Instead, the greater volatility appears to be attributable to private information revealed in trading and to temporary price deviations induced by specialist and other traders. The implied cost of immediacy at the open is significantly higher than at the close. Other empirical evidence in this article documents the volume of trading at the open, the time delays between the exchange opening and the first transaction in a stock, the difference in daytime volatility versus overnight volatility, and the extent to which volatility is related to trading volume.